2020
DOI: 10.1007/s13205-020-2072-2
|View full text |Cite
|
Sign up to set email alerts
|

Cross-amplification of microsatellite markers across agarwood-producing species of the Aquilarieae tribe (Thymelaeaceae)

Abstract: Tree species in the Aquilarieae tribe of the Thymelaeaceae family produce agarwood, a natural product highly valued for its fragrance, but the species are under threat due to indiscriminate harvesting. For conservation of these species, molecular techniques such as DNA profiling have been used. In this study, we assessed cross-amplification of microsatellite markers, initially developed for three Aquilaria species (A. crassna, A. malaccensis, and A. sinensis), on ten other agarwood-producing species, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 35 publications
0
7
1
Order By: Relevance
“…In the present study, the transferability observed (9.05%) was similar to the average of approximately 10% reported in cross-genera transferability studies of eudicots between 1997 and mid-2006 ( Barbará et al, 2007 ). However, the percentage transferability determined here was lower than the cross-genera amplification percentage observed in some families, such as Bignoniaceae (40.58%) ( Kalia et al, 2020 ) and Cactaceae (35.16%) ( Bombonato et al, 2019 ), and much lower than that between species within the same genus ( Miranda et al, 2020 ; Pern et al, 2020 ; Li et al, 2021 ). The transferability of SSR markers between species or genera is determined by the conservation of DNA sequences and the stability of primer binding sites in flanking regions of SSRs during evolution ( Ellegren, 2000 ; Saeed et al, 2016 ).…”
Section: Discussioncontrasting
confidence: 76%
“…In the present study, the transferability observed (9.05%) was similar to the average of approximately 10% reported in cross-genera transferability studies of eudicots between 1997 and mid-2006 ( Barbará et al, 2007 ). However, the percentage transferability determined here was lower than the cross-genera amplification percentage observed in some families, such as Bignoniaceae (40.58%) ( Kalia et al, 2020 ) and Cactaceae (35.16%) ( Bombonato et al, 2019 ), and much lower than that between species within the same genus ( Miranda et al, 2020 ; Pern et al, 2020 ; Li et al, 2021 ). The transferability of SSR markers between species or genera is determined by the conservation of DNA sequences and the stability of primer binding sites in flanking regions of SSRs during evolution ( Ellegren, 2000 ; Saeed et al, 2016 ).…”
Section: Discussioncontrasting
confidence: 76%
“…However, in other places, the farmers have changed their cultivation techniques in order to grow this plant to yield leaves by trimming the tree to keep it small, similar to a tea tree. 4,5…”
Section: Introductionmentioning
confidence: 99%
“…However, in other places, the farmers have changed their cultivation techniques in order to grow this plant to yield leaves by trimming the tree to keep it small, similar to a tea tree. 4,5 Apart from agarwood, the leaves of Aquilaria have traditionally been used as a herbal tea for laxative, anti-inflammatory, sedative, and pain-relieving purposes. 6 It has been widely reported that Aquilaria leaves are a very rich source of polyphenols, such as xanthones, flavonoids, and benzophenones.…”
Section: Introductionmentioning
confidence: 99%
“… 2018 ; Pern et al. 2020 ). In this study, we characterized the complete chloroplast (cp) genome sequence of G. walla to serve as a valuable genomic resource for the conservation effort of this important agarwood-producing plant species and to determine its evolutionary relationship to other genera classified in the Thymelaeaceae.…”
mentioning
confidence: 99%
“…Scientific studies were widely conducted on G. walla after identifying its ability of producing agarwood resins (Subasinghe and Hettiarachchi 2013). However, genetic research on this species is still limited (Eurlings and Gravendeel 2005;Farah et al 2018;Pern et al 2020). In this study, we characterized the complete chloroplast (cp) genome sequence of G. walla to serve as a valuable genomic resource for the conservation effort of this important agarwood-producing plant species and to determine its evolutionary relationship to other genera classified in the Thymelaeaceae.…”
mentioning
confidence: 99%